2014
DOI: 10.1007/s00253-014-6001-3
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic proteins for the enhanced enzymatic hydrolysis of cellulose by cellulase

Abstract: Reducing the enzyme loadings for enzymatic saccharification of lignocellulose is required for economically feasible production of biofuels and biochemicals. One strategy is addition of small amounts of synergistic proteins to cellulase mixtures. Synergistic proteins increase the activity of cellulase without causing significant hydrolysis of cellulose. Synergistic proteins exert their activity by inducing structural modifications in cellulose. Recently, synergistic proteins from various biological sources, inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
65
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(71 citation statements)
references
References 97 publications
0
65
0
6
Order By: Relevance
“…6). These processes could, for example, include the production and attachment of yellow affinity substance, together with the production and activity of bacterial endoglucanases or other cellulose hydrolysis-enhancing proteins (Kim et al 2014), which are probably less well detected than exo-glucanases and β-glucosidases by the cellulase activity assay used (Coleman et al 2007). Regardless of the prior processes involved, there was a clear correlation between the onset of registered cellulase activity and biogas production from the cellulose substrate, indicating that much of the cellulase activity recorded in the assay is derived from expression of β-glucosidases, which are thus presumably the critical enzymes induced between days 4 and 6.…”
Section: Dashed Lines Indicate Fitted Datamentioning
confidence: 99%
“…6). These processes could, for example, include the production and attachment of yellow affinity substance, together with the production and activity of bacterial endoglucanases or other cellulose hydrolysis-enhancing proteins (Kim et al 2014), which are probably less well detected than exo-glucanases and β-glucosidases by the cellulase activity assay used (Coleman et al 2007). Regardless of the prior processes involved, there was a clear correlation between the onset of registered cellulase activity and biogas production from the cellulose substrate, indicating that much of the cellulase activity recorded in the assay is derived from expression of β-glucosidases, which are thus presumably the critical enzymes induced between days 4 and 6.…”
Section: Dashed Lines Indicate Fitted Datamentioning
confidence: 99%
“…Thus, to achieve anaerobic digestion as completely as possible, very long retention times in the anaerobic digester are required [3, 4], which make the capital costs of large volume digesters high. Part of the recalcitrance to hydrolysis can be attributed to the crystallinity of cellulose, which can only be efficiently hydrolyzed, in its simplest form, by a combination of endo- and exo-glucanases together with β-glucosidases [5]. However, it has been found that the crystallinity of cellulose does not completely preclude hydrolysis because it can proceed if appropriate enzymes can access the crystalline cellulose [1].…”
Section: Introductionmentioning
confidence: 99%
“…Synergistic action of these enzymes is vital for complete breakdown of cellulose into soluble sugars (Kim et al 2014). Extensive basic and applied research on cellulases revealed their commercial significance and diverse industrial applicability, especially in bioethanol production (Bajpai 1999;Harman and Kubicek 1998;Uhlig 1998).…”
Section: Introductionmentioning
confidence: 99%